1982
DOI: 10.1136/thx.37.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Catheter drainage of spontaneous pneumothorax: suction or no suction, early or late removal?

Abstract: Twenty-three patients with primary spontaneous pneumothorax and 30 patients with secondary spontaneous pneumothorax treated by intercostal catheter drainage with underwater seal were divided randomly into two groups, one receiving suction drainage (up to 20 cm H20 pressure) and the other no suction. The success rate was 570% for the former and 50 / for the latter. The suction group spent an average of five days in hospital, whereas the non-suction group averaged four days. Suction drainage therefore did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 3 publications
0
36
0
2
Order By: Relevance
“…In a randomized study including 30 patients with SSP, the drainage duration with (up to 20 cm H 2 O) versus without suction was, however, equal [125]. The study also showed that removal of the drain is better with an interval of 2 days rather than immediately after complete re-expansion of the lung (p < 0.1).…”
Section: Evidence Gradementioning
confidence: 81%
See 2 more Smart Citations
“…In a randomized study including 30 patients with SSP, the drainage duration with (up to 20 cm H 2 O) versus without suction was, however, equal [125]. The study also showed that removal of the drain is better with an interval of 2 days rather than immediately after complete re-expansion of the lung (p < 0.1).…”
Section: Evidence Gradementioning
confidence: 81%
“…Indication for using a suction system is also a persistent air leak (more than 48 h with indwelling drainage) with or without incomplete re-expansion of the lung. There is no evidence for the routine use of suction [125][126][127].…”
Section: Evidence Gradementioning
confidence: 99%
See 1 more Smart Citation
“…Applying suction initially did not result in an increased success rate in a study by So and Yu,11 although suction may be tried if there is a PAL. In a randomised trial of 80 trauma patients, the chest tube time was shorter with suction compared with a simple under water seal (72.2 v 92.2 hours, p=0.013) 12.…”
Section: Discussionmentioning
confidence: 94%
“…The So Sy and Yu DYC found ICTD without suction as the better way of the treatment. 22 Suction was not used in our study. Boghaut AB and Patel RB treated 72.5% of the patients with ICTD and 5% with rest.…”
Section: Discussionmentioning
confidence: 99%